Extruded talus treated with reimplantation and primary tibiotalocalcaneal arthrodesis - Mohammad, H; A’Court, J; Pillai, A (Royal College of Surgeons of England, 2017)
Extruded talus is a rare serious result from a high-energy injury to a supinated and plantar flexed foot. Treatment remains controversial with a lack of congruent evidence for talar reimplantation. A 34-year-old woman was involved in a road traffic accident at 40 mph. Imaging revealed a left talus extruded anterolaterally with a talar neck fracture. Additional injuries included right acetabular fracture, transverse process fractures and rib fractures, which were treated conservatively. The talus was reimplanted and the talar neck fixed with a cortical screw. A hindfoot nail was used to fuse the calcaneus, talus and tibia. Follow-up at two years showed solid tibiotalocalcaneal fusion, with no evidence of avascular development, and the patient was fully weight bearing without pain. We believe this is the first published case of successful primary tibiotalocalcaneal fusion for extruded talus injuries.